New Combinations of Rhaponticoides (Asteraceae, Cardueae) from Afghanistan (Global Journal of Science Frontier Research, 2014)
In a forthcoming systematic treatment of Afghanistan species of Rhaponticoides, herbarium collections were examined, and as a result, increased the number species of the genus to 3 spp. for Afghanistan. Morphologically, the species of the genus are classified into three subsections: Iranicae (1 spp.), Ruthenicae (1 spp.) and Turkestanicae (1 spp.) in Afghanistan. Two new combinations are proposed for Centaurea gerhardii and C. turkestanica, and lectotype is designated for R. turkestanica. Finally, a first key of the Rhaponticoides species in Afghanistan is presented here.
Keywords: Afghanistan; identification key; lectotypification; new combinations; Rhaponticoides